Synthesis and toxicity characterization of carbon coated iron oxide nanoparticles with highly defined size distributions - Mendes, Rafael Gregorio; Koch, Britta; Bachmatiuk, Alicja; Gendy, Ahmed A. el; Krupskaya, Yulia; Springer, Armin; Klingeler, Rüdiger; Schmidt, Oliver; Büchner, Bernd; Sanchez, Samuel; Rümmeli, Mark Hermann (Biochimica et biophysica acta. General subjects, 2014)
Background - Iron oxide nanoparticles hold great promise for future biomedical applications. To this end numerous studies on iron oxide nanoparticles have been conducted. One aspect these studies reveal is that nanoparticle size and shape can trigger different cellular responses through endocytic pathways, cell viability and early apoptosis. However, systematic studies investigating the size dependence of iron oxide nanoparticles with highly defined diameters across multiple cells lines are not available yet. - Methods - Iron oxide nanoparticles with well-defined size distributions were prepared. All samples were thoroughly characterized and the cytotoxicity for four standard cell lines (HeLa Kyoto, human osteosarcoma (U2OS), mouse fibroblasts (NIH 3T3) and mouse macrophages (J7442)) where investigated. - Results - Our findings show that small differences in size distribution (ca. 10nm) of iron oxide nanoparticles do not influence cytotoxicity, while uptake is size dependent. Cytotoxicity is dose-dependent. Broad distributions of nanoparticles are more easily internalized as compared to the narrow distributions for two of the cell lines tested (HeLa Kyoto and mouse macrophages (J7442)). - Conclusion - The data indicate that it is not feasible to probe changes in cytotoxicity within a small size range (10nm). However, TEM investigations of the nanoparticles indicate that cellular uptake is size dependent. - General significance - The present work compares narrow and broad distributions for various samples of carbon-coated iron oxide nanoparticles. The data highlights that cells differentiate between nanoparticle sizes as indicated by differences in cellular uptake. This information provides valuable knowledge to better understand the interaction of nanoparticles and cells.
Available online 3 September 2013
Gesehen am 03.11.2020